Saber - School Finance Objectives and Conceptual Approach - World Bank (Washington, DC, 2013)
Education finance has long been a topic of debate. With education consuming a large share of public expenditures in many countries, the public is increasingly interested in how education resources are used. In addition, the economic downturn is prompting many more questions as governments reconsider spending priorities in the context of tightening budgets. The goal of expanding educational opportunity for all students is inextricably linked to questions of education finance: how much do countries invest in education? How do governments support schools? What is the role of the private sector, including households, in education? What are the appropriate financing arrangements for an effective allocation of public funds? How should resources be spent in schools to maximize student learning? Efforts to answer these questions have been an important part of the World Bank's operations and analytical services work in low and middle income countries. Important efforts include regional analyses to document the relationship between per student financing and learning outcomes; operational support for financing arrangements that provide those closer to the point of service delivery with greater control over educational resources; and the development of tools to empower education stakeholders to monitor school budgets and their implementation. While this work has contributed to understanding better education finance policies and practices, much more research is needed to document the policies that are most effective for ensuring equitable, efficient and adequate education spending across and within countries.